Germline mutation rates and the long-term phenotypic effects of mutation accumulation in wild-type laboratory mice and mutator mice - Uchimura, Arikuni; Higuchi, Mayumi; Minakuchi, Yohei; Ohno, Mizuki; Toyoda, Atsushi; Fujiyama, Asao; Miura, Ikuo; Wakana, Shigeharu; Nishino, Jo; Yagi, Takeshi (Genome Research, 2015)
The germline mutation rate is an important parameter that affects the amount of genetic variation and the rate of evolution. However, neither the rate of germline mutations in laboratory mice nor the biological significance of the mutation rate in mammalian populations is clear. Here we studied genome-wide mutation rates and the long-term effects of mutation accumulation on phenotype in more than 20 generations of wild-type C57BL/6 mice and mutator mice, which have high DNA replication error rates. We estimated the base-substitution mutation rate to be 5.4 × 10−9 (95% confidence interval = 4.6 × 10−9–6.5 × 10−9) per nucleotide per generation in C57BL/6 laboratory mice, about half the rate reported in humans. The mutation rate in mutator mice was 17 times that in wild-type mice. Abnormal phenotypes were 4.1-fold more frequent in the mutator lines than in the wild-type lines. After several generations, the mutator mice reproduced at substantially lower rates than the controls, exhibiting low pregnancy rates, lower survival rates, and smaller litter sizes, and many of the breeding lines died out. These results provide fundamental information about mouse genetics and reveal the impact of germline mutation rates on phenotypes in a mammalian population.
10.1101/gr.186148.114